Kenya’s 2022 General Elections and Nigerian’s 2023 General Elections: Any Lessons for Democratic Consolidation in Africa? - Godwin Ojanyi Agbiloko; Gerald Ifeanyi Okafor (International Studies Journal)
Universally, election is the pillar of representative democracy. The health of any democracy, no matter its type or status, depends on a small technical detail: the conduct of elections. Everything else is secondary. A credible election not only confers legitimacy on political leadership, but it is also crucial to the sustenance of democratic order. Paradoxically, the electoral process in Africa has been characterized by violence. In the 21st century, manifestations of electoral violence have assumed an unprecedented magnitude and changing form and character, with negative implications for democratic stability. The level and magnitude of electoral and political violence has risen and the political elites have often converted their foot-soldiers who undermine the electoral process by perpetrating these violent acts. This paper showcases that Kenyans have carved out a roadmap for themselves and democratic reformers across the continent. It further underscores the defining characteristics of the Nigeria’s 2023 general elections with confidence in elections as means of making political choices through constitutional reforms and independent judiciary signposting the salient similarities between the Kenya’s and Nigeria’s general elections. Therefore, the paper seeks to point some dynamics of Kenya’s 2022 as well as highlighting some features in the 2023 elections in Nigeria, which could help in defining democratic governance and democratic consolidation in Africa?